Total Fatty Acids in Murrah Buffaloes Milk on Commercial Farms in Brazil - Fernandes, S. A. A.; Mattos, W. R. S.; Matarazzo, S. V.; Tonhati, Humberto [UNESP]; Gama, M. A. S.; Lanna, D. P. D. (Pagepress Publ, 2007)
The objective of this trial was to document the total fatty acids in Murrah buffaloes milk on commercial farms in Brazil. Data from forty lactating Murrah-crossbred buffaloes were collected on five commercial farms located at Sarapui and Pilar do Sul, São Paulo-Brazil. A field survey was done from April to November 2002. In four farms, buffaloes were fed with wet brewers grains (primary concentrate). Only one farm (Farm 4) offered pasture and corn silage. Monthly milk samples were collected and stored at -20 degrees C until analyzed for fatty acid composition. The fatty acids with the highest percentage in total milk fat were C(16:0); C(18:1c9); C(18:0) and C(14:0). The average content observed in C(16:0) varied from 25.4 to 32.5%. Farm 4 (pasture plus corn silage) showed a higher C(16:0) value (32.5%). C(18:1c9) (varied) from 20.6 to 25.1%, C(14:0) varied from 5.9 to 8.9% and CLA content (C(18:2c9t11)) varied from 1.0 to 1.8%. Farm 3 presented higher average of C(18:1c9) (25.1%) and C(18:2c9t11) (1.8%), and lower average of C(14:0) (6.0%). Likewise, unsaturated fatty acids, C(18:1c9) and C(18:2c9t11) were higher on Farm 3. Probably, these results can be due to high CIA intakes derived from wet brewers grain and pasture. Long chain fatty acids varied from 34.2% (Farm 4) to 48.8% (Farm 3). In general, diets based on pasture and corn silage increased the levels of medium chain fatty acids in Murrah buffaloes milk.
Keywords: Buffalo milk; CLA; Fatty acid profile; Tropical farming